The Safety and Effectiveness of Multi-Segment Cortical Bone Trajectory Screws in Adult Degenerative Scoliosis with Stenosis Among the Elderly: Minimum 5-year Follow-up Study - Wang J; Ding Z; Liu Y; Hai Y (Clinical Interventions in Aging, 2025)
Jie Wang,1,* Zihao Ding,1,* Yuzeng Liu,1 Yong Hai1– 4 1Department of Orthopedic Surgery, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 2Joint Laboratory for Research & Treatment of Spinal Cord Injury in Spinal Deformity, Capital Medical University, Beijing, 100069, People’s Republic of China; 3Laboratory for Clinical Medicine, Capital Medical University, Beijing, 100069, People’s Republic of China; 4Clinical Center for Spinal Deformity, Capital Medical University, Beijing, 100069, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuzeng Liu, Email beijingspine2010@163.com Yong Hai, Email yong.hai@ccmu.edu.cnPurpose: To evaluate the long-term efficacy and safety of multi-segment cortical bone trajectory screws for treating mild adult degenerative scoliosis with stenosis among the elderly.Patients and Methods: From January 2018 to December 2019, a total of 41 patients of mild adult degenerative scoliosis with stenosis underwent posterior lumbar decompression, bone graft fusion, and internal fixation, which were retrospectively divided into pedicle screw (PS) group and cortical bone trajectory (CBT) screw group according to different internal fixation methods. The operation time, intraoperative blood loss, immobilization, and length of hospital stay were compared between the two groups. The visual analog score (VAS) of low back and leg pain, Oswestry disability index (ODI), Cobb angle, lumbar lordosis (LL) angle, apex vertebral translation (AVT), coronal balance distance (CBD) and sagittal vertical axis (SVA) were compared between the two groups preoperatively and 6 months, 1 year, 5 years postoperatively. Perioperative and follow-up complications were observed.Results: The CBT group was superior to PS group in operation time, intraoperative blood loss, immobilization, length of hospital stay (P< 0.05). The low back VAS and ODI in CBT group were significantly lower than those in PS group at 6 months, 1 year and 5 years postoperatively (P< 0.05). The leg VAS in CBT group was lower than PS group at 5 years postoperatively (P< 0.05). The incidence of screw loosening and adjacent segment disease 5 years postoperatively in CBT group was significantly lower than that in PS group (P< 0.05).Conclusion: Multi-segment cortical bone trajectory screws is a safe and effective treatment option for mild adult degenerative scoliosis with stenosis among the elderly. This technique features miniinvasive trauma and quick recovery, which might lead to improved long-term quality of life and a reduction in screw loosening and adjacent segment disease rates.Keywords: cortical bone trajectory screw, adult degenerative scoliosis, stenosis, elderly